A Review of IoT-enabled Smart Street Light Power Management Systems: Challenges and Opportunities - Mayuri Kathe; Sushil Bakhtar (International Journal of Solid State Innovations & Research, 2024)
In the contemporary world, people expect all their demands to be satisfied. To address this human desire, scientific and technological developments are accelerating. One important factor in the quick development of technology is the Internet of Things (IoT). The goal of smart led street lighting systems is to create and implement cutting-edge IOT developments for energy-saving street lighting. Automation of street lighting is the best way to reduce electrical power waste since it eliminates the need for manual lighting system operation. This technique adjusts street light lighting by employing a sensor that uses the least amount of electrical energy possible. At night, when an object is identified, streetlights glow brightest; otherwise, they remain in the dim mode. This technique adjusts street light lighting by employing a sensor that uses the least amount of electrical energy possible. At night, when an object is identified, streetlights glow brightest; otherwise, they remain in the dim mode. The real- time updates of street processing are visualised and changes are notified through the usage of the Internet of Things (IOT). This will lower carbon dioxide emissions, power usage, heat emissions, and maintenance and replacement expenses. Via the internet, one can access real-time street light information (ON/OFF Status) from any location at any time. It guarantees outstanding long-term stability and high dependability. Automated systems are more efficient than manual processes. These gadgets can also be reprogrammed to suit our needs.
Keywords: IR sensor; LDR sensor; LED; Microcontroller (CC3200); bylnk application